Важливість розвитку лідерських якостей студентської молоді - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2024)
Резюме. У статті доведено, що від дій лідерів, керівників, менеджерів залежить ефективне управління різними соціальними структурами, починаючи з груп, колективів підприємств, військових організацій і закінчуючи державою. Побудова будь-якого розвиненого суспільства об’єктивно зумовлює потребу в лідерах. Лідерський стиль управління організацією – тема, яка на слуху в багатьох керівників протягом останнього десятиліття. Потрібні нові гуманістично-орієнтовані молоді лідери, здатні до продуктивного співробітництва, продукування неординарних ідей, готові до прийняття рішень і несення відповідальності за себе та свою діяльність.

Abstract. The article proves that the effective management of various social structures, starting with groups, collectives of enterprises, military organizations and ending with the state, depends on the actions of leaders, managers, and managers. The construction of any developed society objectively determines the need for leaders. The leadership style of managing an organization is a topic that has been on the ears of many managers during the last decade. We need new humanist-oriented young leaders capable of productive cooperation, producing extraordinary ideas, ready to make decisions and take responsibility for themselves and their activities. An important issue is the definition of the qualities that are inherent in successful leaders. The main variants of leadership styles are highlighted: authoritarian, permissive, balanced, democratic, command, etc. The goal of a leader is a strong team, where everyone is a self-sufficient individual, but he is an element of a team in which everyone works for the maximum result of a common cause. The process of team formation has several approaches to the interpretation of content. The main groups of leadership qualities and styles are considered Those of the deep characteristics of the image, which are the most important for the leader, are highlighted. The role of training is shown, with the help of which you can successfully present the necessary theoretical material, as well as practice the necessary skills and forms of behavior. The implementation of trainings can be useful for students of various specialties, and especially for those whose professional activities will be related to interaction with other people. After all, such directions of work of a specialist require developed communication skills and professional skills of interaction with other people, which can be achieved by means of active and interactive training Strategies for developing teacher leadership qualities in the context of educational quality management are key to improving teaching effectiveness and ensuring student success. These strategies are aimed at the development of teacher-leaders who are able not only to effectively manage classroom processes, but also to influence the development of the educational system as a whole.
The importance of developing the leadership qualities of youth students
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015039 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-10
Keywords: лідерські якості; лідерський стиль управління; групи лідерських якостей та стилів; характеристики іміджу; студентська молодь